A novel peer-to-peer personalized advertising framework using ad hoc wireless communication - Lok, Jing Ming; Wong, Daniel Kuok-Shoong (2005)
The proliferation of mobile devices and pervasiveness of wireless technology have provided a new environment for mobile commerce (M-Commerce).In this environment, mobile advertising will be playing an important role in mobile commerce marketing. Generally, mobile advertising can be defined as advertising a product advertisement or a service advertisement to the mobile users via wireless network.This paper discusses some issues in mobile advertising and proposes a framework for mobile advertising using peer-to-peer ad hoc wireless communications.